2009
DOI: 10.1037/a0015456
|View full text |Cite
|
Sign up to set email alerts
|

The milieu of managerial work: An integrative framework linking work context to role requirements.

Abstract: Theoretical and empirical efforts focusing on the interplay between work context and managerial role requirements have been conspicuously absent in the scholarly literature. This paucity exists despite over 60 years of research concerning the requirements of managerial work and with the rather universal recognition that work context meaningfully shapes organizational behavior. The authors developed a theoretical model linking different types of role requirements to different forms of work context. They empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
213
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(222 citation statements)
references
References 137 publications
9
213
0
Order By: Relevance
“…More recently, research on job design and job analysis has begun to incorporate intrafirm (e.g., organizational climate) and interfirm forces (e.g., occupational context) (Dierdorff & Morgeson 2007Dierdorff et al 2009) into the theory of job design and job analysis. From an OP/OB perspective, these recent developments are important on the basis of two perspectives.…”
Section: Job Design and Job Analysismentioning
confidence: 99%
“…More recently, research on job design and job analysis has begun to incorporate intrafirm (e.g., organizational climate) and interfirm forces (e.g., occupational context) (Dierdorff & Morgeson 2007Dierdorff et al 2009) into the theory of job design and job analysis. From an OP/OB perspective, these recent developments are important on the basis of two perspectives.…”
Section: Job Design and Job Analysismentioning
confidence: 99%
“…Dierdorff, Rubin, and Morgeson (2009) found that task context is predictive of role/job requirements. Furthermore, Morgeson, Dierdorff, and Hmurovic (2010) explain how occupational context can "influence the relationships between work design features and various outcomes" (p. 351), yet they argue despite its importance, this has been understudied in regards to the effects of job characteristics.…”
Section: Job Typementioning
confidence: 99%
“…Beyond their importance in regulating managerial behaviour, managerial roles have implications for task performance (Dierdorff et al, 2009;Dierdorff & Morgeson, 2007;Katz and Kahn, 1978;Morgeson et al, 2005). The degree of fit between managers' role behaviour and the role requirement of organizational tasks determines whether those tasks are tied to appropriate managers having the right knowledge base, experience and access to relevant information (Das, 2001;Dierdorff et al, 2009;Morgeson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our focus here is, therefore, to investigate how managerial responsibilities for trade show tasks, constituting objective setting, trade show selection and booth management, affect the marketing performance of trade show marketers using insights from organizational role theory (Dierdorff et al, 2009;Katz and Kahn, 106 1978), the functionalist perspective of managerial roles (Floyd & Lane, 2000) and the trade show management literature (Kijewski et al, 1993;Tanner & Chonko, 1995). Managerial roles, in the functionalist perspective are viewed as sets of structured work related expectations ascribed to different levels of management (Floyd & Lane, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation